Harmful cyanobacterial blooms in Slovenia - Bloom types and microcystin producers - Bojan Sedmak; Gorazd Kosi (Acta Biologica Slovenica, 2002)
Up to now, research on cyanobacteria and their biologically active substances has been directed principally towards their harmful effects on humans, and little has been done to elucidate their ecological role. In order to understand better the biological success of cyanobacterial blooms, and in order to be able to compare the results of different scientific investigations, we must find and agree on a definition of the phenomenon. We propose a definition of harmful cyanobacterial blooms based on the OECD boundary system of eutrophication with the addition of phycocyanin values. We have found a direct linkage between the trophic conditions in the water-bodies and the frequency of formation of cyanobacterial blooms. Specific toxic species and their strains have been studied intensively. However, in order to elucidate the mechanisms that enable cyanobacteria to overtake eutrophic water bodies we must change our approach. Cyanobacterial blooms should not be treated merely as different species or strains but as superorganisms. It is their intraspecific diversity that permits cyanobacteria to be successful in a variable water environment. Wehere focus attention on microcystin producers and microcystins as an adaptation to the limited light conditions, which arise in cyanobacterial blooms. The conclusions are illustrated with some data from surface water-bodies in Slovenia.